Incidencia de la actividad física en el estado nutricional de los estudiantes de la Unidad Educativa Adolfo María Astudillo - Quiñonez Moran, Gina Lisseth (2021)
Physical education classes have changed with this new way of giving and receiving classes, educational institutions have changed from face-to-face to virtual and their interactions are limited so that only the practice of physical activity is emotional and students should be put into practice in isolation and without greater control than that of their parents, showing health problems for students caused by lack of exercise and poor nutrition. The objective of this research work is aimed at analyzing how physical education influences the nutrition of the students of the Adolfo María Astudillo school in the city of Babahoyo, for which the potentialities of physical education and the possibilities were theoretically based that can be applied to develop sports habits related to nutrition .. For the development of the study, the research methodology was used, composed of the design that expresses its qualitative and cross-sectional approach, then there is the modality that is documentary and field, followed by the type of descriptive research, the methods that are inductive- deductive and analytical-synthetic, data collection techniques such as observation, anthropometric assessment and surveys, applied to a sample of 80 students, the results showed that physical education does influence sports motivation and nutrition of the students and the construction of a training program related to eating and nutritional habits was proposed.